Development and Performance Evaluation of Biomass-Based Injera Baking Gasifier Stove: A Case Study of Clean Cooking Technologies in Ethiopia - Dawit Tessema Ebissa; Eshetu Getahun (The Scientific World Journal, 2024)
The primary energy source in Ethiopia is biomass. Over 80% of Ethiopians are rural dwellers who rely on biomass energy for lighting and cooking. In most parts of Ethiopia, injera is traditionally baked using an open fire, a three stone, or a device using woody biomass. These baking stoves have very low efficiency and consume a significant amount of fuel. Moreover, these traditional baking stoves have released large amounts of indoor air pollution, which has led to different types of health-related risks, especially for women and children in the country. Therefore, the aim of this study was to investigate efficient and fuel-saving injera baking technologies. Rigorously, an injera baking gasifier stove was designed, developed, and characterized in detail through water boiling and control cooking test methods. The indoor air pollution level was evaluated using particulate matter measuring instruments. The result indicated that the developed gasifier stove had a thermal efficiency of 21.8%. Furthermore, an 86% fuel savings performance was demonstrated by the controlled cooking test for the injera baking gasifier stove. The average emission concentrations of particulate matter and carbon monoxide were 608 µg/m3 and 9 ppm, respectively, during indoor air pollution determination. The study showed that injera baking gasifier stoves are a promising cooking technology for societies where baking is mostly dependent on traditional biomass fuel.